Ionization Constants of Four Dinitrophenols in Water at 25 °C - Robinson, Robert A. (J Res Natl Bur Stand A Phys Chem, 1960)
Thermodynamic ionization constants of 2,3-, 2,5-, 3,4-, and 3,5-dinitrophenols in aqueous solution at 25° C have been determined by a spectrophotometric method. The respective values found, expressed as pK, are 4.95(9), 5.21(0), 5.42(2), and 6.69(2). pK has also been determined potentiometrically for 2,3- and 3,5-dinitrophenols; the respective values obtained are 4.98 and 6.66. The experimental pK values for all six dinitrophenols are lower than the calculated values based on pK data for phenol and the mononitrophenols. Spectral absorption curves are presented for the ionized and unionized forms of the four dinitrophenols.